2022
DOI: 10.1039/d1ee02714j
|View full text |Cite
|
Sign up to set email alerts
|

Solar fuels: research and development strategies to accelerate photocatalytic CO2 conversion into hydrocarbon fuels

Abstract: Photocatalytic CO2 conversion is vital technology to realize global carbon neutrality and generate future energy supplies. This review proposes fundamentals, challenges, strategies, and prospects for photocatalytic CO2 conversion research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
277
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(277 citation statements)
references
References 433 publications
(396 reference statements)
0
277
0
Order By: Relevance
“…Coupling CO 2 reduction and H 2 O oxidation over photocatalysts using solar energy is an appealing strategy to alleviate the greenhouse effect and simultaneously produce value-added chemicals or fuels 1 , 2 . In recent decades, photocatalytic studies have almost exclusively focused on semiconductors, which provide an opportunity for reducing CO 2 with H 2 O at room temperature 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Coupling CO 2 reduction and H 2 O oxidation over photocatalysts using solar energy is an appealing strategy to alleviate the greenhouse effect and simultaneously produce value-added chemicals or fuels 1 , 2 . In recent decades, photocatalytic studies have almost exclusively focused on semiconductors, which provide an opportunity for reducing CO 2 with H 2 O at room temperature 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the Pb-free halide double perovskites and 2D layered perovskites are also promising in the field of photocatalysis due to their large electronic bandgap and stability. 211 For instance, Zhou et al synthesized Cs 2 AgBiBr 6 nanocrystals that were shown to be stable for more than three weeks in a low polarity medium under light-soaking and 55% relative humidity. 242 Double perovskites with B = Bi and B ′ = Ag have the highest rate of H 2 evolution that reaches 380 μmol g −1 h −1 when supported on carbon doped with nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The main requirements for a promising photocatalytic material are suitable band alignments and bandgaps, strong light absorption, high chemical stability, efficient charge carrier transport, and good operation in strong acidity and/or alkali environments. [211][212][213] Over the past few years, the potential of Pb-based halide perovskites has been investigated as a catalyst for photocatalytic hydrogen (H 2 ) evolution, CO 2 reduction reaction, and various organic synthesis or chemical reactions. 212,214 The performance of a complete water splitting system can be evaluated by introducing the solar-to-hydrogen (STH) conversion efficiency.…”
Section: Photo-catalysismentioning
confidence: 99%
“…The numbers of photogenerated electrons (e − ) and protons (H + ) available for photocatalytic CO 2 reduction affect product selectivity. [1] The reduction of CO 2 to a specific product requires a specific reduction potential, as shown in Table 1. The reduction capacity of photoexcited electrons must be sufficient to trigger the desired reduction reaction to preferentially generate a desired product.…”
Section: Product Selectivity Of Sacs For Co 2 Reductionmentioning
confidence: 99%
“…Recycling undesirable CO 2 into functional chemical compounds is recognized as an ambitious approach to addressing global environmental and energy issues. [1][2][3][4] However, the direct capture and conversion of CO 2 from the atmosphere is challenging since only four CO 2 molecules are available for every ten thousand air molecules. Fortunately, plants are effective at converting CO 2 into carbohydrates and oxygen; and researchers, inspired by natural photocatalysis, have explored numerous artificial ways of converting CO 2 into carbonaceous compounds.…”
Section: Introductionmentioning
confidence: 99%